A maize ADP‐ribosylation factor ZmArf2 increases organ and seed size by promoting cell expansion in Arabidopsis. Issue 1 (20th August 2015) - Wang, Qilei; Xue, Xiaojing; Li, Yuling; Dong, Yongbin; Zhang, Long; Zhou, Qiang; Deng, Fei; Ma, Zhiyan; Qiao, Dahe; Hu, Chunhui; Ren, Yangliu
Abstract : ADP‐ribosylation factors (ARFs) are small GTP‐binding proteins that regulate a wide variety of cell functions. Previously, we isolated a new ARF, ZmArf2, from maize ( Zea mays ). Sequence and expression characteristics indicated that ZmArf2 might play a critical role in the early stages of endosperm development. In this study, we investigated ZmArf2 function by analysis of its GTP‐binding activity and subcellular localization. We also over‐expressed ZmArf2 in Arabidopsis and measured organ and cell size and counted cell numbers. The expression levels of five organ size‐associated genes were also determined in 35S:: ZmArf2 transgenic and wild‐type plants. Results showed that the recombinant ZmArf2 protein purified from Escherichia coli exhibited GTP‐binding activity. Subcellular localization revealed that ZmArf2 was localized in the cytoplasm and plasma membrane. ZmArf2 over‐expression in Arabidopsis showed that 35S:: ZmArf2 transgenic plants were taller and had larger leaves and seeds compared to wild‐type plants, which resulted from cell expansions, not an increase in cell numbers. In addition, three cell expansion‐related genes, AtEXP3, AtEXP5 and AtEXP10, were upregulated in 35S:: ZmArf2 transgenic lines, while the expression levels of AtGIF1 and AtGRF5, were unchanged. Collectively, our studies suggest that ZmArf2 has an active GTP‐binding function, and plays a crucial role in growth and development in Arabidopsis through cell expansion mediated by cell expansion genes.